Increasing Production Yield With Through Feasibility Investment Analysis in Plastic Recycling Industry - Sophian, Ade; Hasbullah, Hasbullah (Journal of Industrial Engineering & Management Research, 2021)
The plastics recycling industry in Indonesia can only fill 82% of national needs. Based on the Survey of this study, plastic recycling industries around Jakarta have a capacity of 80% of their ability. In failure to achieve production capacity, this article aims to increase production yield. By investigating a plastic recycling industry in Bogor with about 320 Kg/hour production from 400 Kg/hour capacity, this study aims to improve the output at Geording Machine Line by replacing old machines, which most contributed to the failure of production yield. In Production Line consists of five Work Stations (WS): WS-1, WS-2, WS-3, WS-4, and WS-5, having bottlenecks of 78.00 minutes that shall be 60 minutes ideally to produce 400 kg/hour on WS-4. Feasibility of Investment Analysis shows that buying a new machine for WS-4 makes it feasible to prevent more loss in failure production yield.